Family as a Source of Forming Axiological System of Youth. Coherence Between Value Systems of Parents and Children - Wojciechowska, Mariola (Journal of Vasyl Stefanyk Precarpathian National University, 2020)
The paper examines the importance of the family as an educational environment for the formation of the value system of the young generation. It is an outcome of cyclical research on the values of the younger and older generation in the Świętokrzyskie Voivodeship in Poland. The research data refer to the value examination questionnaire "100 Sentences - 100 Opinions" by Mirosław J. Szymański and the Value Scale by Milton Rokeach. The results confirm significant similarity of axiological systems for both respondent groups. The comparison of research results from three study stages (1994, 2003 and 2017) proves that the values systems in both younger and older generation are more constant than variable. Therefore, it can be concluded that in spite of disruptions experienced by a contemporary family, it is still considered the source of principles and values for a younger generation. The author proves that the first positions in the young people's and their parents axiological systems are held by the allocentric and prosocial values. This is also confirmed by the appreciation of the value of "true friendship" and "mature love”. It is beyond doubt that these values make it possible today to establish close and rewarding relationships that are extremely helpful to the sense of security and recognition. Furthermore, the studies prove that the participants in both research groups perceived the civic and material values as least important. The research studies a rather moderate acceptance by the respondents of the views representing family values. Young people in particular, still refer to the family with reluctance, criticising the various areas of the family's life, and they do not hesitate to point out the factors that disorganise the life of this community. They also clearly indicate their expectations of the family and, as can be anticipated, construct their own visions of the family. Although there are some changes in the order of values, they are not clear enough to suggest that the hierarchy of values and reference to family values of younger and older respondents has changed significantly over the years. The results with regard to the meaning of the family as a source of the young generation's values somewhat undermine the common theses about the little impact of family socialisation on the development and upbringing of the young generation and the loss of the family's basic duties.